United Nations Security Council’s Role in the Liberation War of Bangladesh: Critical Analysis - Hasan, Mehabub; Al Mamun, Firoz; Amin, Ruhul; Islam, Hafizul; Islam, Monirul (PT. Riset Press International, 2024)
Bangladeshis began their fight for independence on March 26, 1971, as a response to Pakistani rule that was unfair to their race and treated them like a colony within their own country. Between the start of the Liberation War and November, the UNO's main job was to provide aid and support for civilians. When India and Pakistan went to war on December 3 over the Liberation War, the UN Security Council got very busy. The Security Council met nonstop during this time and discussed many ideas and counter-proposals. Two superpowers of this time, USA and the Soviet Union, took opposing positions in the Security Council. United States and China sided with Pakistan while Soviet Union sided with Bangladesh (East Pakistan). In the Security Council, France and Britain remained neutral and did not vote. The Security Council could not reach a consensus. After debate and vote in the Security Council, the agenda was transmitted to the General Assembly on 6 December. General Assembly passed a 'Unity Formula for Peace' resolution by an overwhelming majority on December 7. India and Bangladesh rejected this idea; therefore, the US called a second Security Council session. The Security Council met from 12 to 21 December at various times. Bangladesh's independence on December 16 altered everything. International representatives acknowledged reality and unanimously approved a ceasefire agreement on December 21, resolving the long-awaited Bangladesh problem.